2020
DOI: 10.3390/antiox9111115
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Tricyclic Pyridine Alkaloids from Fusarium lateritium SSF2, against Glutamate-Induced Oxidative Stress and Apoptosis in the HT22 Hippocampal Neuronal Cell Line

Abstract: Excessive glutamate damages neuronal cells via the accumulation of intracellular reactive oxygen species (ROS), calcium ion (Ca2+) influx, depolarization of mitochondrial membrane potential, and apoptosis, which may result in the development of chronic neurodegenerative diseases. In this study, we evaluated the effects of 4,6′-anhydrooxysporidinone isolated from endophytic fungus Fusarium lateritium SSF2 on glutamate-induced cytotoxicity, accumulation of intracellular ROS, increases in superoxide anion product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The effect is mediated via the inhibition of glutamate-induced oxidative stress and apoptosis. In this study, low concentrations of 2.5 and 5 µM SSF2-2 were effective [17]. The anticancer effects of compounds isolated from F. lateritium SSF2 have not been explored to date.…”
Section: Introductionmentioning
confidence: 79%
“…The effect is mediated via the inhibition of glutamate-induced oxidative stress and apoptosis. In this study, low concentrations of 2.5 and 5 µM SSF2-2 were effective [17]. The anticancer effects of compounds isolated from F. lateritium SSF2 have not been explored to date.…”
Section: Introductionmentioning
confidence: 79%
“…Neurons are the functional unit of the nervous system [ 21 23 ]. The oxidative stress induced by glutamate will trigger the changes in the structure and function of the neurons and cause the death of neurons [ 14 , 24 ]. Earlier studies showed that plant extracts and compounds with strong antioxidant activity protected glutamate-induced neuronal death [ 4 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 75 ] isolated tricyclic pyridine alkaloids including (1) 6-deoxyoysporidinone (SSF2-1), (2) 4,6′-anhydrooxysproridinone (SSF2-2), and (3) sambutoxin (SSF2-3) from Fusarium lateritium (SSF2). Furthermore, SSF2-1, SSF2-2, and SSF2-3 were evaluated for their protective effects against glutamate-induced HT22 cell death.…”
Section: Neuroprotective Studies and Proposed Molecular Mechanismmentioning
confidence: 99%
“…The compound SSF2-2 showed the significant protective effects against HT22 cells from cytotoxicity induced by glutamate, it reduces the intracellular accumulation of ROS, increases in superoxide anion production, Ca 2+ influx, and depolarization of mitochondrial membrane potential. Additionally, the compound SSF2-2 increased the expression of Nrf2 and HO −1 pathways, whereas inhibited the apoptotic cell death via inhibition of cytochrome c and cleaved caspase-9, -3 in glutamate-induced HT22 cells [ 75 ]. Choi and co-workers, isolated and identified six neuroprotective bioactive compounds present in an endophytic fungi Fusarium solani JS-0169 collected from the leaves of Morus alba [ 76 ].…”
Section: Neuroprotective Studies and Proposed Molecular Mechanismmentioning
confidence: 99%